Long‐term study of lisdexamfetamine dimesylate in Japanese children and adolescents with attention‐deficit/hyperactivity disorder. Issue 1 (8th December 2019) - Ichikawa, Hironobu; Miyajima, Tasuku; Yamashita, Yushiro; Fujiwara, Masakazu; Fukushi, Akimasa; Saito, Kazuhiko
Abstract: Aims: As an extension of a phase 2/3 study evaluating the efficacy and safety of lisdexamfetamine dimesylate (LDX) 30, 50, or 70 mg/d for 4 weeks in Japanese patients aged 6‐17 years with attention‐deficit/hyperactivity disorder (ADHD), this study evaluated its long‐term safety and efficacy. Methods: This was a multicenter, open‐label study of LDX for 53 weeks. Safety was assessed by regular medical examination for treatment‐emergent adverse events (TEAEs); regular recording of body weight, vital signs, and laboratory test values; and completion of dependence questionnaires. Efficacy was assessed using Japanese versions of the ADHD‐Rating Scale‐IV (ADHD‐RS‐IV) and Conners' 3rd edition Parent Rating Scale (Conners 3); plus Clinical Global Impression‐Improvement (CGI‐I), Clinical Global Impression‐Severity, and Parent Global Assessment (PGA) scales. Results: Of 132 enrolled patients, 104 completed the trial. Most frequent treatment‐related TEAEs were decreased appetite (73.5%), initial insomnia (39.4%), and weight decrease (22.0%). Most TEAEs were mild (82.6% of patients). There were no serious or severe TEAEs or deaths. No treatment‐related TEAEs were associated with blood pressure or pulse rate, and no patient had a QTcF interval >500 ms. Statistically significant improvement from baseline to week 53 was observed in the mean ADHD‐Rating Scale‐IV total score and mean Conners 3 subscale scores. Most patients showed improvement on the CGI‐I (78%) and PGA (76.5%) scales. Conclusions: No significant safety issues were observed with LDX 30, 50, or 70 mg/d administered for 1 year in Japanese children and adolescents with ADHD. LDX was associated with long‐term reductions in ADHD symptoms and severity. Abstract : This multicenter, open‐label study evaluated the long‐term safety and efficacy of lisdexamfetamine dimesylate (LDX) in Japanese patients aged 6‐17 years with attention‐deficit/hyperactivity disorder. No significant safety issues were observed with LDX 30, 50, or 70 mg/d administered for 1 year. There were no serious or severe treatment‐emergent adverse events (TEAEs) or deaths. The most frequent treatment‐related TEAEs were decreased appetite, initial insomnia, and weight decrease. TEAEs were mild in 82.6% of patients.